Recolonization : GATT, the Uruguay Round & the Third World - Raghavan, Chakravarthi; Nyerere, Julius K. (London Penang, Malaysia : Zed Books Third World Network, 1990)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: ontwikkelingslanden; wereldhandel